2013
DOI: 10.3324/haematol.2012.080895
|View full text |Cite
|
Sign up to set email alerts
|

Impact of disease status and stem cell source on the results of reduced intensity conditioning transplant for Hodgkin's lymphoma: a retrospective study from the French Society of Bone Marrow Transplantation and Cellular Therapy (SFGM-TC)

Abstract: ABSTRACTsupported by the role of donor lymphocyte infusions, although data are conflicting. 9 In contrast, reduced intensity conditioning is associated with an acceptable rate of non-relapse mortality in the most recently published studies and has, therefore, improved the prognosis of patients with refractory/relapsed Hodgkin's lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 29 publications
1
22
2
1
Order By: Relevance
“…Although the number of patients who received a RIC regimen was small in our study, we also observed an even higher incidence of NRM compared to those who received myeloablative conditioning regimens (57% vs. 44%). This is in contrast to the three studies including HD patients TBI‐based RIC UCBT without ATG where the 2 and 3‐yr NRM incidence account for 13–22%. So far, these studies included a lower proportion of chemo‐resistant patients (8–12%) than in our study (26%).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Although the number of patients who received a RIC regimen was small in our study, we also observed an even higher incidence of NRM compared to those who received myeloablative conditioning regimens (57% vs. 44%). This is in contrast to the three studies including HD patients TBI‐based RIC UCBT without ATG where the 2 and 3‐yr NRM incidence account for 13–22%. So far, these studies included a lower proportion of chemo‐resistant patients (8–12%) than in our study (26%).…”
Section: Discussioncontrasting
confidence: 70%
“…So far, these studies included a lower proportion of chemo‐resistant patients (8–12%) than in our study (26%). Several studies supported that chemo‐resistant disease at transplant was the most important factor related with superior NRM irrespectively of the conditioning and the source of stem cells used .…”
Section: Discussionmentioning
confidence: 99%
“…2A). Recently, many studies have mainly used reducedintensity conditioning for allogeneic HSCT, and most of these patients had previously undergone autologous HSCT [15][16][17]. Sureda et al compared the outcomes of allogeneic HSCT for patients with relapsed and refractory HL with myeloablative conditioning to those with reduced-intensity conditioning [18].…”
Section: Discussionmentioning
confidence: 99%
“…Marcais et al reported a 39% OS rate and an 18% PFS rate for chemorefractory disease compared to patients in CR, who had a 70%-74% OS rate and a 40%-51% PFS rate at 3 years [26]. In our study, 36 patients were in CR and 25 patients were without remission.…”
Section: Discussionmentioning
confidence: 51%